Application of European design principles to cross laminated timber. (15th September 2018) - Fink, Gerhard; Kohler, Jochen; Brandner, Reinhard
Highlights: Basis of design principles for cross laminated timber. Uncertainties related to the production procedure of CLT. Difficulties of non-standardized test procedure of CLT. Abstract: The design of cross laminated timber (CLT) structures is not included in the current version of European structural timber design standards of EN 1995 (Eurocode 5, EC 5). Due to the increasing importance of CLT, in different applications such as complete wall or floor elements as well as girders, it is one of the main goals of the currently ongoing revision of EC 5 to provide design principles for CLT structures. In the present paper some general aspects, relevant for the implementation of CLT in European standards in order to be consistent with the general philosophy of the Eurocodes are summarized and discussed. The differences between standard test specimens and structural components as well as the uncertainties related to the production procedure of CLT and the non-standardized test procedure are discussed. An investigation of 12 different test series from five different producers clearly indicates a large variation between different production series. Based on the investigation from the test series a reliability analysis is performed. The results indicate that the same partial safety factor as recommended for glued laminated timber (GLT) is appropriate in order to achieve an acceptable reliability. However, the analysis also indicates the potential for a smaller partial safety factor in the future, in case that the production of CLT is standardized and appropriate standardized test methods for the individual material properties exist.